Staffing foreign subsidiaries with parent country nationals or host country nationals? Insights from European subsidiaries - Christoph Dörrenbächer; Jens Gammelgaard; Frank McDonald; Andreas Stephan; Heinz Tüselmann (Hochschule für Wirtschaft und Recht Berlin, IMB Institute of Management Berlin, 2013)
This paper investigates the relationship between the use of parent company nationals (PCN) and home country nationals (HCN) and various attributes in foreign owned subsidiaries in Denmark, Germany and the UK. The study explores whether the existing literature on international staffing adequately captures the effects of PCN verses HCN managers on key characteristics of subsidiaries. The results of the study indicate that the PCN/HCN dichotomy widely used in the international staffing literature needs to take account of the following issues: First: The study confirms theoretical assumptions based on social capital theory that subsidiaries led by HCNs are more embedded in the host country's external environment (by having more frequent relationships with host country customers, suppliers and competitors). However, the study reveals that the assumed advantages PCN led subsidiaries have with headquarters do not extend to their relationships with competitors in other parts of the MNC. Second: HCN led subsidiaries are more autonomous than PCN led subsidiaries with regard to operational and strategic decisions that relate to the market issues (market areas supplied, product range) and with respect to the local institutional environment (HRM). Our study finds that this is also the case with regard to strategic decisions on financial control as well as on R&D and new product development. Third: On average, HCN led subsidiaries perform significantly better than PCN led subsidiaries with regard to sales growth by value, productivity and innovation. This is in line with the findings of Beechler et al. (2005), the only other study investigating European subsidiaries. It also confirms the study of Konopaske et al. (2002). However, it contradicts the findings of Segiguchi et al. (2011) and Bebenroth and Li (2010) on the same matter. – – Dieser Aufsatz untersucht die Auswirkungen unterschiedlichen Managementbesatzes in ausländischen Tochtergesellschaften in Dänemark, Deutschland und Großbritannien. Im Ergebnis wird gezeigt, dass die in der Literatur vorzufindende Dichotomie zwischen lokalen Managern und Expatriates (Stammhausdelegierte) nur eingeschränkt haltbar ist. So kann u.a. gezeigt werden, dass sich angenommene Fühlungsvorteile von Expatriates nicht auf Schwestergesellschaften beziehen und dass lokale Manager nicht nur hinsichtlich marktrelevanter Entscheidungen, sondern auch bezogen auf die Finanzkontrolle sowie Forschungs- und Entwicklungsaktivitäten eine größere Autonomie besitzen. Auch hinsichtlich verschiedener Leistungskriterien wie wertmäßiges Umsatzwachstum, Produktivität und Innovationsrate schneiden ausländische Tochtergesellschaften, die von lokalen Managern geleitet werden, besser ab als Tochtergesellschaften, die von Expatriates geleitet werden.
Keywords: 650